GJMPBU 2021
DOI: 10.25259/gjmpbu_10_2021
|View full text |Cite
|
Sign up to set email alerts
|

A Review Study of the Role of Socioeconomic Status and its Components in Children’s Health

Abstract: The impact of socioeconomic status (SES) on children is among the most debated issues in human rights. By reviewing the literature, this study aims to identify socioeconomic mechanisms affecting children’s health. The child’s economic operations are influenced by adults. According to several studies, children from middle- and high-SES families, unlike low-SES children, have precise and logical policies, because their parents provide logical explanations in response to their children, and consequently, their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Discussions may focus on the importance of these questions in identifying patterns of health behaviors and practices related to breastfeeding, the incidence of childhood illnesses, and participation in family planning programs. This findings are in line with previous research showing a link between certain behaviors and the health of children and families [25], [26], [26]- [37], [37].…”
Section: Based On the Results Of Validity And Reliability Tests Insupporting
confidence: 93%
“…Discussions may focus on the importance of these questions in identifying patterns of health behaviors and practices related to breastfeeding, the incidence of childhood illnesses, and participation in family planning programs. This findings are in line with previous research showing a link between certain behaviors and the health of children and families [25], [26], [26]- [37], [37].…”
Section: Based On the Results Of Validity And Reliability Tests Insupporting
confidence: 93%
“…The current study showed similar results. Therefore, low socioeconomic status deleteriously affects children's neurodevelopment [37,38]. In addition, parental socioeconomic status can play an important role in whether children are provided appropriate sociocultural and economic environments, including accessibility and support for medical services, education, food, and other daily expenses, which could impact growth and development both before and after birth.…”
Section: Plos Onementioning
confidence: 99%
“…The socioeconomic status (SES) of a child's parents, as indicated by variables such as parental educational attainment, occupational level, income, and prosperity (e.g., Davis‐Kean et al, 2021), has an important impact on the child's development. Family SES is positively associated with mental and physical health (see Baharvand et al, 2021; Balaj et al, 2021; Kamalulil & Panatik, 2021; Poulain et al, 2020, for recent reviews). Moreover, it is well established that a high SES has favorable effects on the development of social and cognitive skills (and underlying brain structures and functions), and on the child's academic and occupational achievements (e.g., see Lawson et al, 2018; Noble et al, 2021, and below).…”
Section: Introductionmentioning
confidence: 99%